Mesiodens- A Report of Two Cases - Maharaj, Anuranjan; Mukherjee, Chitrita Gupta; Anand, Prerna; Kumar, Arvind (Nepal Journal of Health Sciences, 2022)
Teeth more than normal in number are termed as supernumerary. The presence of multiple supernumerary teeth is termed ‘mesiodentes’. Supernumerary tooth usually results in oral problems such as malocclusion, food impaction, poor aesthetics, and cyst formation. This paper presents a case report on the successful management of mesiodens and mesiodentes.